2002
DOI: 10.1076/jcen.24.3.294.983
|View full text |Cite
|
Sign up to set email alerts
|

Bereavement-Related Cognitive Impairment in an Oldest-Old Community-Dwelling Brazilian Sample

Abstract: As it is already known that depression can cause a demonstrable impact on cognition in elderly subjects, the objective of this study was to determine whether also the mourning process is associated with any cognitive impairment in this age range. A random and representative sample (a sample with 77 subjects/total county population of oldest-old with 219 subjects = 35%) aged 80 years or more was selected from the county of Veranópolis in the Brazilian rural southern region. Of this group, the cognitive function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 13 publications
(13 reference statements)
2
28
0
1
Order By: Relevance
“…We additionally examine a range of outcomes previously associated with widowhood including mental health (19,20), cognitive health (21), and physical health markers, such as mobility and instrumental activities of daily living (22); we examine these outcomes both before and after spousal bereavement to inform several mechanistic pathways simultaneously. Determining the cause and mechanism of the “widowhood effect” is important for the development of interventions to alleviate excess mortality.…”
Section: Objectivementioning
confidence: 99%
“…We additionally examine a range of outcomes previously associated with widowhood including mental health (19,20), cognitive health (21), and physical health markers, such as mobility and instrumental activities of daily living (22); we examine these outcomes both before and after spousal bereavement to inform several mechanistic pathways simultaneously. Determining the cause and mechanism of the “widowhood effect” is important for the development of interventions to alleviate excess mortality.…”
Section: Objectivementioning
confidence: 99%
“…In individuals aged 65-80, widow(er) hood is an independent predictor of cognitive decline, even when controlling for physical functioning and depressive symptoms (Aartsen, Van Tilburg, Smits, Comijs, & Knipscheer, 2005). Neuropsychological functioning in bereaved individuals aged 80-95, compared with a matched nonbereaved sample (Xavier, Ferraz, Trentini, Freitas, & Moriguchi, 2002), showed that bereavement was longitudinally associated with worsened cognitive performance, specifically involving attention and memory. This decreased performance could not be explained by greater symptoms of depression.…”
Section: Correlates Of Complicated Griefmentioning
confidence: 99%
“…Our study underscores the importance of assessing social, neuropsychological and biological factors that may underlie the occurrence of complicated grief or may result from prolonged exposure to a normal grief reaction. The neuropsychological differences between persons with and without complicated grief were more modest than in clinical studies (Xavier et al 2002;Ward et al 2007;Maccallum & Bryant, 2010;Rosnick et al 2010;Corruble et al 2011;O'Connor & Arizmendi, 2014). Thus, any clinical implications must be inferred cautiously.…”
Section: Resultsmentioning
confidence: 88%
“…Compared with either normal-grief or no-grief groups, participants with complicated grief performed worse in domains of executive function, and information processing speed, and had a lower total brain volume as measured by structural brain imaging. The few previous studies of bereavement and cognition demonstrated poorer memory performance and attention in persons with normal grief, but did not specifically examine complicated grief (Xavier et al 2002;Ward et al 2007;Rosnick et al 2010;Corruble et al 2011). Two other studies examined the emotional Stroop Test in persons with complicated grief, demonstrating that participants have more cognitive interference compared with no-complicated-grief participants (Maccallum & Bryant, 2010;O'Connor & Arizmendi, 2014).…”
Section: Discussionmentioning
confidence: 94%